'Enslaving Christians': Greek slaves in late medieval Cyprus. Issue 1 (2nd January 2016) - Dincer, Aysu
Abstract : This article explores the functions and perceptions of slavery in late medieval Cyprus, paying particular attention to attitudes towards Christian, and especially, Greek slaves. The island had a predominantly Orthodox population, and received a substantial influx of Greek slaves in the fourteenth and fifteenth centuries. Evidence from notarial accounts, estate surveys and chronicles is utilized to examine the ways in which 'Greek' slaves were defined and identified. The article investigates whether belonging to this perceived group played a part in shaping the slaves' paths towards manumission. The context (urban or rural) in which Christian slaves served also influenced attitudes towards labour use in various ways.